1999
DOI: 10.1103/physrevc.59.3324
|View full text |Cite
|
Sign up to set email alerts
|

Size of fireballs created in high energy heavy ion collisions as inferred from Coulomb distortions of pion spectra

Abstract: We compute the Coulomb effects produced by an expanding, highly charged fireball on the momentum distribution of pions. We compare our results to data on Au+Au at 11.6 A GeV from E866 at the BNL AGS and to data on Pb+Pb at 158 A GeV from NA44 at the CERN SPS. We conclude that the distortion of the spectra at low transverse momentum and mid-rapidity can be explained in both experiments by the effect of the large amount of participating charge in the central rapidity region. By adjusting the fireball expansion v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[36] concluded that: the SIS data are consistent with V C = 27 MeV corresponding to a freeze-out radius of 8 fm, the AGS data are consistent with a radius of 10 fm, and the early SPS data (NA44) are consistent with a 9 fm radius. A full transport model calculation [38,39] was also applied to these data. In that analysis, the freezeout radius was also found to be 10 fm for the AGS and SPS data sets.…”
Section: Introductionmentioning
confidence: 99%
“…[36] concluded that: the SIS data are consistent with V C = 27 MeV corresponding to a freeze-out radius of 8 fm, the AGS data are consistent with a radius of 10 fm, and the early SPS data (NA44) are consistent with a 9 fm radius. A full transport model calculation [38,39] was also applied to these data. In that analysis, the freezeout radius was also found to be 10 fm for the AGS and SPS data sets.…”
Section: Introductionmentioning
confidence: 99%
“…The cited paper[18] also contains a description of various works made in the past on electromagnetic effects in low and high energy nuclear collisions. For more details on this subject, see[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
mentioning
confidence: 99%
“…Indeed, these effects turned out to be ubiquitous in heavy-ion collisions, ranging from SIS beam energies [6,7,8], to AGS [9,10], SPS [11], and even up to RHIC energies, as discussed in an extensive report [10]. The early theoretical work done to interpret the Bevalac data [4,5] was taken up again as the SIS, AGS, and SPS results became available [12,13,14,15,16]. In particular at low bombarding energies, the π − /π + ratio is expected to provide information on the symmetry term of the nuclear equation of state [17], thus requiring the Coulomb effect to be under full control [18].…”
Section: Introductionmentioning
confidence: 99%